Differentiated instruction in higher education: the experience and perceptions of five academics - Preston, Melly; Subban, Pearl; Suprayogi, Muhamad Nanang; Liyani, Annisa Nanda; Ratri, Andrea Prita Purnama (Journal of Education and Learning (EduLearn), 2025)
The increasing diversity of students in higher education presents numerous advantages for the sector, yet it also imposes substantial challenges for educators. This study explored the experiences of five academics across two countries as they strive to implement differentiated instruction (DI) to accommodate the diverse needs of students. The primary objective is to identify five aspects of DI implementation, namely teaching strategies, challenges, strategies to overcome challenges, methods to evaluate, and educators' perceptions. The study employs a qualitative research design, utilizing semi-structured interviews for data collection. The results of the study revealed that educators agreed that implementing DI requires quite a lot of resources from educators, such as time for preparation and planning, effort, and commitment. On the other hand, they also struggle with other obligations as administrators in their workplace. Experienced and junior educators employed distinct methods to address challenges, with the former utilizing forward planning and the latter concentrating on refining their skills in DI. Despite these variations, there is a common shared understanding among all educators that although implementing DI poses challenges, it remains both manageable and beneficial within the diverse higher education environment.